Analysis of Student Self-Regulation in Differentiated Learning with Atomic Model Material: A Case Study of Junior High School Students - Zakiya, Umi Sayidatus; Nurhayati, Nurhayati; Rahmat, Adi; Hamdiyati, Yanti; Winarno, Nanang (Journal of Science Education Research, 2025)
Differentiated learning is one of the learning strategies that can be applied to the Kurikulum Merdeka. This approach is expected to maximize individual progress and create a more positive learning experience. This research aims to determine the profile of students' self-regulation and its relationship to the application of a differentiated learning approach. There were 135 research subjects obtained through a purposive sampling technique with the criteria being that students received learning using a differentiated approach to atomic material models. Data collection used research instruments adapted from the Learning and Study Strategies Inventory (LASSI) to measure students' self-regulation, as well as formative assessment scores to determine the scores resulting from the differentiated approach to atomic material models. Based on descriptive analysis and correlation tests using Pearson's product-moment correlation analysis techniques, the results showed that there was no significant positive relationship between the application of a differentiated approach to student self-regulation (p > 0.05 and r = 0.012). However, the self-regulation variable shows a score in the quite good category of 6.67% and the good category of 93.33%. This shows that students' self-regulation profiles tend to be at a good level.